Mallards Anas platyrhynchos shot in Eastern Poland: ecological risk evaluated by analysis of trace elements in liver. Issue 8 (17th November 2019) - Sujak, Agnieszka; Wiącek, Dariusz; Jakubas, Dariusz; Komosa, Andrzej; Kitowski, Ignacy
Abstract: Mallard Anas platyrhynchos is a numerous and widespread duck of Northern Hemisphere. In some regions, it is an important component of the diet of local inhabitants. It may also serve as an effective bioindicator of pollutions in aquatic environments. In this study, we investigated trace elements concentrations in livers of 23 Mallards shot at fish pond complex during wintering in the Lublin region (SE Poland). The element concentrations followed the pattern: Fe >Mg  > Ca > Zn > Cu > Mn > Se > Sr > Cd > Pb > Cr > V > Hg > As > Ni > Sc. Our study revealed lack of sex differences in hepatic element concentrations suggesting similar wintering areas of both sexes. At 8.7% of the examined individuals concentration of Pb was classified as subclinical toxicity or moderate clinical poisoning for Mallards. It indicates serious need for banning of the use of Pb hunting ammunition in those parts of Europe (in that in Poland) where it is still allowed. Such the ban should be established at least in wetlands and waterbodies. Groups of people especially prone to elevated concentration of toxic elements (e.g., pregnant women, children) should avoid consumption of meat originated from wildfowl.